A epístola de Tiago: a relação entre fé e obra. - Vieira, Rosinaldo Ernesto (2018)
This research had as its main goal to make an analysis of the Epistle of James, contextualizing the historical understanding of justification and salvation by faith, and the theological consequences of the relationship between faith and works for a practical and significant Christianity. It comprises three chapters. The first one presents the background to the Epistle of James in order to situate its reading and discussion in chapter 2, which deals with the issue of faith and works by establishing its meaning in the Bible and in the Epistle of James. Chapter 3 deals with a Christian way of life based on the exhortations of the Epistle so that the brethren live a practical faith that is coherent with their discourse, and valuable to personal relationships and charity.